Perceptions of the cancer care left undone in primary and community services: A mixed methods evaluation. (13th May 2020) - Lawler, Jessica; Leary, Alison; Lofton, Lydia; Bushe, Dave
Abstract: Primary and community care in the United Kingdom are under increasing workforce and time pressures. How these pressures affect the delivery of cancer care has rarely been explored. This service evaluation aimed to elucidate some of the views of the workforce in this sector of what work in cancer care is left undone, and what they would like to be able to offer more of. An exploratory sequential design was taken including a questionnaire and interviews asking primary and community care staff in London about their workload in cancer care. Surveys were analysed using descriptive statistics. The evaluation revealed a perception from primary and community care that there is work in cancer care that is currently being left undone. 64% of the workforce across all professions reported that they worked 10 or more hours of unpaid overtime per week. Respondents identified psychological care for people with cancer (PWC), and bereavement care for families and carers of PWC as the most common areas that were left undone. They would like to do more proactive work, in place of the current reactive 'fire‐fighting' they are doing. For example, signposting available services to PWC and access to nutritional support. There was a desire for acknowledgement of the time and workforce pressures in primary and community care, and how these are hindering the delivery of care for PWC.